2019
DOI: 10.1177/1474515119889770
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification model for post-stroke pneumonia in patients with acute ischemic stroke

Abstract: Background: Post-stroke pneumonia (PSP) has been implicated in the morbidity, mortality, and increased medical costs after acute ischemic stroke. Aim: The aim of this study was to develop a prediction model for PSP in patients with acute ischemic stroke. Methods: A retrospective, case-control, secondary analysis study was conducted using data for 10,034 patients with ischemic stroke who presented to the hospital within 24 hours of onset of stroke symptoms. The predictive factors for PSP were analyzed using mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…Furthermore, patients with documented dysphagia screening were more likely to have a medical history (ie, atrial fibrillation, current smoking) that could increase the risk of pneumonia. 37 Meanwhile, our results demonstrate that the dysphagia status as a result of the dysphagia screening was also associated with a higher risk of in-hospital death (adjusted OR: 6.13, 95% CI: 5.18–7.27), which is consistent with other studies. 5 , 23 , 31 …”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, patients with documented dysphagia screening were more likely to have a medical history (ie, atrial fibrillation, current smoking) that could increase the risk of pneumonia. 37 Meanwhile, our results demonstrate that the dysphagia status as a result of the dysphagia screening was also associated with a higher risk of in-hospital death (adjusted OR: 6.13, 95% CI: 5.18–7.27), which is consistent with other studies. 5 , 23 , 31 …”
Section: Discussionsupporting
confidence: 92%
“…The third article, “Risk stratification model for post-stroke pneumonia in patients with acute ischemic stroke,” deals with the development of a prediction model for post-stroke pneumonia (PSP) in patients with acute ischemic stroke. 11 Here, the authors identified factors such as the National Institute of Health Stroke Scale score at admission, pulse rate at admission, and percentage of lymphocytes, as important for stratifying the risk of PSP. Applying the risk stratification model will allow healthcare providers to recognize high-risk patients early and undertake interventions to reduce PSP.…”
mentioning
confidence: 99%
“…Therefore, the high INR at admission may be the end-point expression of the release of inflammatory factors. Secondly, a previous study found that the patients with higher INR had a more serious stroke ( 25 ) which was related to the increased risk of infection after stroke ( 11 , 28 , 29 ). Moreover, patients with severe stroke were often accompanied by reduced consciousness, which was a risk factor for SAP ( 30 ).…”
Section: Discussionmentioning
confidence: 98%